ANALISIS KEPUASAN PENGGUNA TERHADAP KUALITAS WEBSITE TALKABOT INDONESIA MENGGUNAKAN METODE WEBQUAL 4.0, IMPORTANCE PERFORMANCE ANALYSIS, DAN CUSTOMER SATISFACTION INDEX (STUDI KASUS: PT. LOGIKA BERBICARA INDONESIA) - Allvira Arianti Amir Hamzah (2021)
Technologic growth is very fast and rapid. Talkabot Indonesia uses the website as a medium for disseminating information and a platform for potential clients to know the services and products available at Talkabot Indonesia. However, the function of the Talkabot Indonesia website there are still many aspects that must be considered, such as the information and appearance. Thus, it is necessary to analyze the website quality assessment based on user ratings to find out how the quality of the Talkabot Indonesia website using the WebQual 4.0 framework which includes the dimensions of usability (usability), information quality (quality of information), and service interaction quality (quality of service interaction). Quantitative methods were used to collect survey data, then distribute questionnaires based on a sampling technique from a population of purposive random sampling. Testing the research data is carried out by testing the validity, reliability and sample paired t - test, then analyzing the data by analyzing the value of the gap between the actual assessment and the assessment of user expectations, WebQual Index (WQI) to get the website quality value, and calculating the Importance Performance Analysis (IPA). The number of samples in this study were 162 male or female respondents aged > 18 years domiciled in DKI Jakarta and West Java and employees of Talkabot Indonesia. Based on the actual assessment and assessment of user expectations to get recommendations for improvement of the Talkabot Indonesia website. Keyword: Importance Performance Analysis, Customer Satisfaction Index, WebQual 4.0,